Analysis of Digital Transformation Readiness in State-Owned Construction Enterprises Based on the INDI 4.0 Measurement Framework - Ernawan; Christina Juliane (Jurnal Penelitian Pendidikan IPA, 2025)
Digital transformation is a strategic necessity for state-owned construction companies in the face of global competition and the demands of operational efficiency. This study aims to evaluate the readiness of digital transformation of PT. PQR uses the Indonesia Industry 4.0 Readiness Index (INDI 4.0) framework which includes five pillars: Management and Organization, People and Culture, Products and Services, Technology, and Business Operations. The research method used a descriptive quantitative approach with an action research design through questionnaires of 53 respondents (executives, managers, and specialists) and in-depth interviews, analyzed using descriptive statistics and thematic analysis. The results of the study showed an average score of 3.51 from a target of 4.00, placing PT. PQR in the category of ready readiness towards full implementation. The pillar scores show: Management and Organization (3.92), People and Culture (3.75), Products and Services (3.00), Technology (3.83), and Business Operations (2.89). The biggest gap is in the Business Operations pillar with partial automation and suboptimal intelligent maintenance systems. Key challenges include limited human digital competencies, organizational cultural resistance, budget constraints, and weak external collaboration. The research recommends strengthening digital governance, increasing human resource capacity through structured programs, investment in enabler technologies (cloud, AI, IoT), and ecosystem collaboration. Academically, the research contributes to the literature on the implementation of INDI 4.0 in the SOE construction sector; Practically, it is a reference for a sustainable digital transformation strategy.